2019
DOI: 10.1038/s41388-019-0779-5
|View full text |Cite
|
Sign up to set email alerts
|

Tumor microenvironment defines the invasive phenotype of AIP-mutation-positive pituitary tumors

Abstract: The molecular mechanisms leading to aryl hydrocarbon receptor interacting protein (AIP) mutation-induced aggressive, young-onset growth hormone-secreting pituitary tumors are not fully understood. In this study, we have identified that AIP-mutation-positive tumors are infiltrated by a large number of macrophages compared to sporadic tumors. Tissue from pituitary-specific Aip-knockout (AipFlox/Flox;Hesx1Cre/+) mice recapitulated this phenotype. Our human pituitary tumor transcriptome data revealed the “epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 68 publications
(60 reference statements)
1
65
0
Order By: Relevance
“…Inhibited tumor cell growth and intracellular Ca 2+ flux [138] shRNA-CCL5 silencing, anti-CCR5 antibody Inhibited the invasive capacity of CSLCs, inhibited invasion of ovarian cancer stem-like cells in vitro and in tumor xenografts [59] Anti-CCL5 antibody Decreased tumor growth and invasion induced by CAFs [139] Reduced epithelial-mesenchymal transition-like process of non-stem ovarian cancer cells, metastasis in xenografts [140] Anti-CCL5 antibody, shRNA-CCL5 silencing Inhibited endothelial cell differentiation and tube formation of cancer stem-like cells in vitro and in xenografts [141] Pancreatic cancer Maraviroc Decreased tumor cell growth and invasion [51] Decreased tumor cell Inhibited, induced apoptosis in vitro, reduced liver metastasis from xenografts [142] Pituitary tumor Maraviroc Decreased macrophage migration induced by tumor cells [143] Prostate cancer…”
Section: Anibaminementioning
confidence: 99%
See 1 more Smart Citation
“…Inhibited tumor cell growth and intracellular Ca 2+ flux [138] shRNA-CCL5 silencing, anti-CCR5 antibody Inhibited the invasive capacity of CSLCs, inhibited invasion of ovarian cancer stem-like cells in vitro and in tumor xenografts [59] Anti-CCL5 antibody Decreased tumor growth and invasion induced by CAFs [139] Reduced epithelial-mesenchymal transition-like process of non-stem ovarian cancer cells, metastasis in xenografts [140] Anti-CCL5 antibody, shRNA-CCL5 silencing Inhibited endothelial cell differentiation and tube formation of cancer stem-like cells in vitro and in xenografts [141] Pancreatic cancer Maraviroc Decreased tumor cell growth and invasion [51] Decreased tumor cell Inhibited, induced apoptosis in vitro, reduced liver metastasis from xenografts [142] Pituitary tumor Maraviroc Decreased macrophage migration induced by tumor cells [143] Prostate cancer…”
Section: Anibaminementioning
confidence: 99%
“…Pituitary tumors with mutated-aryl hydrocarbon receptor interacting protein have an aggressive phenotype [186]. This tumor is characterized by an intratumoral accumulation of macrophages and high levels of CCL5 expression compared to sporadic adenomas or normal pituitary [143]. Macrophages secrete molecules that induce EMT and enhance the invasiveness of mutated cancer cells.…”
Section: Pituitary Tumorsmentioning
confidence: 99%
“…Finally, since familial cases of pituitary germline mutations responsible for the pathogenesis of PitNETs have been described, such as those in MEN1 or AIP, and such mutations may be present in a sporadic setting and correlate with tumor aggressiveness since tumors with MEN1 or AIP mutations have been reported to be resistant to conventional treatment [178]. Of note, a recent report indicated that MMP2 and MMP9 are upregulated in AIP-positive PitNETs and may confer a more aggressive phenotype [179]. In AIP-positive tumors, a significant number of altered mesenchymal-to-epithelial transition (EMT) associated genes, including epithelial markers (CDH1, CTNNB1, ERSP1, and EPCAM) and transcriptional (ZEB1) and post-transcriptional regulators (ESRP1) has been identified, suggesting that disruption of the EMT pathway may be responsible for a more aggressive phenotype.…”
Section: Pathological and Molecular Considerationsmentioning
confidence: 99%
“…While germline and somatic mutations in the genes encoding for PKA regulatory subunits have been characterized, they are infrequent and little is known about nongenomic effectors of aberrant PKA activity in human tumors [7,8,25]. The role of the tumor microenvironment in shaping the phenotype of AIP-mutation-positive somatotroph tumors recently been highlighted [26]. We therefore hypothesized that the decreased vascular density observed in acromegalic pituitary tumors may contribute to the activated PKA found in the absence of stimulating gsp mutations.…”
Section: Introductionmentioning
confidence: 99%